PENERAPAN SISTEM ADMINISTRASI BMN PENGADILAN AGAMA: ANALISIS HUKUM EKONOMI SYARIAH - Swedia Disya Citta; Mochamad Sumpena (KASBANA, 2026)
State Property (BMN) plays a strategic role in supporting government administration and public services, including in the context of religious courts. Along with bureaucratic reform and the development of information technology, BMN management has transformed through the implementation of a digital-based administration system. However, the implementation of the system should not be assessed solely on administrative grounds, but also on its conformity with the principles of Islamic economic law. This study aims to analyze the implementation of the BMN administrative system in religious courts and examine its conformity with Sharia economic law. The novelty of this research lies in integrating digital-based BMN governance analysis with the perspective of Sharia economic law in the context of religious courts, a topic that has been relatively rarely studied in previous research. This study uses normative-empirical legal methods, drawing on both legal and conceptual approaches. Data was obtained through the analysis of laws and regulations and related literature, as well as interviews with seven informants who were directly involved in the management of BMN in religious courts. The data was analyzed qualitatively using descriptive-analytical techniques. The results of the study show that the BMN administration system has been implemented in accordance with applicable provisions and supported by information technology, thereby improving administrative order, data accuracy, and accountability. From the perspective of Islamic economic law, this system aligns with the principles of trust, justice, transparency, and public benefit. This research contributes to the development of a study of public asset governance oriented towards Sharia values. Keywords: State Property, Religious Courts, Administrative System, Islamic Economic Law, Accountability.